Exopolysaccharide is required by Paraburkholderia phytofirmans PsJN to confer drought-stress tolerance in pea - Prihatna, Cahya; Yan, Qing (Frontiers in Microbiology, 2024)
Paraburkholderia phytofirmans PsJN is a plant symbiotic bacterium that can colonize a broad spectrum of plant hosts and frequently shows beneficial effects on plant growth. Exopolysaccharide (EPS) is known to be important in plant-bacteria interactions. Previously, we reported that EPS is required for PsJN to survive from drought stress and colonize in pea (Pisum sativum) under drought condition. However, whether EPS is necessary for PsJN to promote plant growth remains unknown. In this work, a comparative study was conducted between the wild-type PsJN and its ∆bceQ mutant that lacks EPS to investigate the role of EPS in PsJN to confer drought-stress tolerance on pea plant. Our results showed that wild type PsJN, but not the ∆bceQ mutant, promoted pea seed germination and seedlings growth under drought stress. Pea plants inoculated with the wild type PsJN had a higher level of drought tolerance, as shown by a better vegetative growth and enhanced nodule formation, than plants inoculated with the ∆bceQ mutant. Moreover, EPS plays a role in the plant colonization under drought stress, because the ∆bceQ mutant was unable to colonize pea seeds and roots as effective as the wild type PsJN. Further, expression of the EPS biosynthesis genes in the bceOVN operon of the wild type PsJN was induced by the presence of glucose. Overall, this study demonstrated that PsJN